Socio-Demographic Patterns of Hypertension and its Association with Tobacco use in Nepal: Evidence from the Country Representative Demographic and Health Survey - Joshi, Yadav Prasad; Aryal, Arjun; Thapa, Rubi; Paudel, Prakriti; Maharjan, Prakriti; Acharya, Krishna Prasad (A Bi-annual South Asian Journal of Research & Innovation, 2025)
Introduction: Cardiovascular diseases (CVDs) account for a third of global deaths, with growing burdens in South Asia. Hypertension is a leading modifiable CVD risk factor, and tobacco use—smoked and smokeless—remains common in Nepal. We examined the association between tobacco use and hypertension and described sociodemographic patterns of hypertension using nationally representative data.Methods: We analysed Nepal Demographic and Health Survey (NDHS) 2016 data, as the data of 2022 were not available while requesting the data access through DHS and drafting this manuscript in late 2022 to early 2023. For prevalence by sociodemographic characteristics (age, province, ecological zone, residence, education, wealth), we included 10,470 adults aged 15–49 years with valid blood pressure (BP) measures (6,364 women; 4,106 men). For tobacco–hypertension associations, 40 participants lacked tobacco data; thus, analyses used 10,430 individuals (6,344 women; 4,086 men). BP was measured three times with validated devices; the mean of the second and third readings defined categories (normal, pre-hypertension, Stage 1–3). Hypertension was SBP ≥140 mmHg and/or DBP ≥90 mmHg or antihypertensive use. We employed descriptive statistics and Chi-square tests and logistic regression for the association of hypertension with any tobacco use (p